Phytochemical Study And In Vitro Antimicrobial Activity Of Pistacialentiscusl. In Boumerdes Mountainous Region (algeria) - Bendifallah, L.; Benmahfoud, A. E.; Hameni, Y.; Mameche, S. (University of Eloued جامعة الوادي, 2014)
Pistacialentiscus L.(Pistaciaceae) is among themost important medicinalplantsin Algeria that is known for its antifungal and antimicrobial properties. For this study, the leaves were collected from the mountainous region of Boumerdes, in northern Algeria. In such a propitious context, the aim of this study was to enhance Pistacialentiscusas a medicinal herb. For their antimicrobial activity, extracts of tannin and polyphenols werescreenedagainst three pathogenic bacterial strains and one pathogenic yeast strains. The phytochemical analysis results showed a remarkable combination of chemical components including a high content in tannins, in leucoanthocyanins, in glucosids, alcaloids, flavonoïds and in saponosids. The tannins and the polyphenols have strong antimicrobial activity against some species.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 02
Keywords: Pistacialentiscus; leaves;phytochemistry;biological activity.